ANALISIS DAN PEMODELAN STRUKTUR GEDUNG RUMAH SAKIT PADA WILAYAH GEMPA TINGGI - I Putu Adi Sadu Gunawan; I Wayan Giatmajaya; I Gede Gegiranang Wiryadi (Fakultas Teknik Universitas Mahasaraswati Denpasar, 2021)
This hospital building structure modeling for providing information about modeling techniques and analysis of the structure of a building with concrete materials and a special moment frame system. The lowrise building is designed to have four levels, function as a hospital, moderate site class conditions, and is located in high seismic areas. The design following the standard code so as to produce a safe and comfortable building. Modeling and structural analysis are using SAP2000 software version 19 to obtain the forces acting on the structure, deflection and deformation. The scope of modeling techniques includes dimension estimation, loading, material, deflection and deformation control, and final dimensions. The preliminary dimensions are determined based on a practical approach for beams, columns and plates based on the provisions of SNI 2847: 2013. The deflection or deformation is controlled for each beam and slab for each floor which is a maximum of 5.4mm less than the allowable deflection of 22mm. The maximum deformation is viewed on each floor for earthquake load based on SNI 1726: 2012. The maximum deformation floor to floors that occurs is smaller than the allowable deformation. The final dimensions obtained are 15cm plate thickness, column K1 60/60 cm, K2 55/55 cm, K3 50/50 cm and K4 45/45cm, beam dimensions B1 40/60 cm, B2 35/50 cm, B3 30/50 cm. Deflection and deformation are following the criteria of SNI 2847-2013, 1726-2012, SNI 1727-2013.